Когда D>0 уравнение имеет 2 корня
Когда D<0 уравнение не имеет корней
Когда D=0 уравнение имеет 1 корень
1)6х²+х-7=0
D=1-4×6×(-7)=169 D>0- 2 корня
Корень из 169=13
Х1=(-1+13)÷12=1
Х2=(-1-13)÷12=-14÷12=-1⅙
2)х²-4х+3=0
D=16-4×3=16-12=4 D>0 -2 корня
Корень из 4=2
Х1=(4+2)÷2=3
Х2=(4-2)÷2=1
Когда D>0 уравнение имеет 2 корня
Когда D<0 уравнение не имеет корней
Когда D=0 уравнение имеет 1 корень
1)6х²+х-7=0
D=1-4×6×(-7)=169 D>0- 2 корня
Корень из 169=13
Х1=(-1+13)÷12=1
Х2=(-1-13)÷12=-14÷12=-1⅙
2)х²-4х+3=0
D=16-4×3=16-12=4 D>0 -2 корня
Корень из 4=2
Х1=(4+2)÷2=3
Х2=(4-2)÷2=1